Ber (Ziziphus mauritiana L.) Based Agri-horti System: A Sustainable Land Use for Arid Ecosystem - Saroj, P. L.; Dhandar, D. G.; Sharma, B. D.; Bhargava, R.; Purohit, C. K. (Indian Journal of Agroforestry, 2020)
The ber (Ziziphus mauritiana L.) based cropping system was initiated under irrigated conditions of hot arid ecosystem of western Rajasthan to quantify the potential of the system. In situ budded ber cv Gola with three spacings (6x6m, 8x8m and 16x4m) as overstorey component and groundnut (Arachis hypogia) - wheat (Triticum aestivam), cluster bean (Cyamopsis tetragonoloba) - mustard (Brassica compestris) and Indian aloe (Aloe barbadensis) as groundstorey components were integrated into the system. Results revealed that in the initial stage of its establishment, there was no competition between groundstroey and overstorey components for resources. Instead, the inputs applied for the groundstorey crops enhanced the vegetative vigour of the ber plants than sole plantation. The ber plants grown with Indian aloe were more vigorous due to the higher level of inputs, Particularly irrigation water that Indian aloe received as compared to the other combinations. In the third year of its plantation, the ber plants came in bearing and yielded 14.44. 8.13 and 8.23 qha-1 fruits under 6x6m, 8x8m and 16x4m, respectively. Among different crop combinations, the highest yield of ber was recorded with Indian aloe (13.55 qha-1) while with groundnut-wheat and cluster bean-mustard, the yield level was almost at par (9.62 and 9.80 qha-1, respectively) and minimum yield was recorded under sole plantation (8.09 qha-1). The average yield of groundstorey crops over two years was recorded as 3.48, 50.97, 10.05, 11.49 and 20.8 qha-1 in groundnut (dry pods), cluster bean (green pods), wheat and mustard (grain) and Indian aloe (green leaf pads), respectively. The biomass production under different groundstorey crops was also recorded and recycled in the same proportion after decomposition from where they were harvested. The investigation revealed that cluster bean - mustard and Indian aloe can be integrated as a compatible groundstorey component with ber as compared to groundnut – wheat, which is a dominant rotation in the irrigated hot arid ecosystem. However, the system needs to be assessed for long-term sustainability from productivity, profitability, soil improvement and practical feasibility point of view fer adoption by the farming community of the region.